2019
DOI: 10.1097/md.0000000000018225
|View full text |Cite
|
Sign up to set email alerts
|

The role of hydroxyurea to prevent silent stroke in sickle cell disease

Abstract: Background: Chronic blood transfusions are standard of care for stroke prevention in sickle cell disease but is not cost effective and not without risks. Hydroxyurea has emerged as an option in the prevention of silent stroke in sickle cell disease. Objective: To evaluate the role of hydroxyurea in preventing silent strokes in a systematic review by adhering to the Cochrane guidelines. Methods: PubMed, EMBAS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 16 publications
1
10
0
1
Order By: Relevance
“…These occur in children with SCD younger than age 6 and increase in occurrence with age. A study showed that 27% of children with SCD younger than age 6 experienced SCI and by the age of 14, 37% of children with SCD experienced SCI [ 40 ]. A similar study in an adult population of patients with SCD with a relatively low mean age of 30 years showed that 53% had brain lesions consistent with SCI [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These occur in children with SCD younger than age 6 and increase in occurrence with age. A study showed that 27% of children with SCD younger than age 6 experienced SCI and by the age of 14, 37% of children with SCD experienced SCI [ 40 ]. A similar study in an adult population of patients with SCD with a relatively low mean age of 30 years showed that 53% had brain lesions consistent with SCI [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although these two treatments have been shown to improve chronic and acute SCD, both require strict adherence, limiting the scope of patients who can be treated via these methods. In addition to the recommended routine adherence, regular blood exchange transfusions are costly and can put patients with SCD at further risk for disease progression by causing iron overload [ 22 , 40 ]. ROS are produced by excess iron via the Fenton reaction, exacerbating SCD symptoms of blood component toxicity [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Folic acid in association with acetylsalicylic acid was used in 2 patients (16.6%). A systematic review conducted by Hasson et al 23 found insufficient evidence to prove hydroxyurea's ability to prevent stroke in patients with sickle cell disease. However, hydroxyurea has been shown to be a viable option, because it is well-tolerated, lower cost, and has fewer side effects relative to regular blood transfusion.…”
Section: Discussionmentioning
confidence: 99%
“…Las transfusiones crónicas de componentes sanguíneos se consideran el estándar de cuidado para la prevención de accidentes cerebrovasculares, a pesar de presentar riesgos como la sobrecarga de hierro y la aloinmunización (39,40). Teniendo en cuenta los riesgos y la costoefectividad se prefieren alternativas como la hidroxiurea, la cual parece ser segura y efectiva.…”
Section: Tratamientounclassified